2020
DOI: 10.1002/da.23104
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal structural neuroimaging markers of risk and recovery from posttrauma anhedonia: A prospective investigation

Abstract: Background: Anhedonic symptoms of posttraumatic stress disorder (PTSD) reflect deficits in reward processing that have significant functional consequences. Although recent evidence suggests that disrupted integrity of fronto-limbic circuitry is related to PTSD development, including anhedonic PTSD symptoms (posttrauma anhedonia [PTA]), little is known about potential structural biomarkers of long-term PTA as well as structural changes in fronto-limbic pathways associated with recovery from PTA over time. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…Using DTI and structural imaging in the weeks following trauma exposure, research has shown that reduced fractional anisotropy of the uncinate fasciculus at around the time of trauma predicted greater PTSD symptoms (in particular posttraumatic anhedonia) at 12 months post-trauma. Furthermore, as the traumatized participants were followed over time, increased gray matter volume of the vmPFC was also associated with reduced trauma-related symptoms over the 12 months following trauma [157]. In another study recruiting patients after trauma exposure with mild traumatic brain injury, smaller cortical volumes of superior frontal cortex and rostral and caudal cingulate at 2 weeks after trauma exposure contributed to the prediction of increased likelihood of 3-month PTSD diagnosis in multivariable models incorporating other established risk factors [158].…”
Section: Structural Imaging In Pfc and Ptsdmentioning
confidence: 98%
“…Using DTI and structural imaging in the weeks following trauma exposure, research has shown that reduced fractional anisotropy of the uncinate fasciculus at around the time of trauma predicted greater PTSD symptoms (in particular posttraumatic anhedonia) at 12 months post-trauma. Furthermore, as the traumatized participants were followed over time, increased gray matter volume of the vmPFC was also associated with reduced trauma-related symptoms over the 12 months following trauma [157]. In another study recruiting patients after trauma exposure with mild traumatic brain injury, smaller cortical volumes of superior frontal cortex and rostral and caudal cingulate at 2 weeks after trauma exposure contributed to the prediction of increased likelihood of 3-month PTSD diagnosis in multivariable models incorporating other established risk factors [158].…”
Section: Structural Imaging In Pfc and Ptsdmentioning
confidence: 98%
“…The experts recommended longitudinal studies to ascertain the course of covid-related PTSD, to identify factors associated with PTSD, and to determine protective measures that can promote better outcomes [12] . These efforts might be supported when we are better able to utilize emerging biomarkers, multimodal early indicator assessment, and machine learning technology to increase the diagnostic accuracy of acute stress responses in order to prevent PTSD [13][14][15][16][17] .…”
Section: The Mental Health Impact Of Covid-19mentioning
confidence: 99%
“…These results also lend support to the idea that executive dysfunction contributes to the maintenance of PTSD [ 7 , 35 ] and above-average EF may be a protective factor. Previous work has also identified executive dysfunction as a risk factor for developing PTSD [ 63 , 64 ] and better EF as indicative of improved treatment outcomes and less dropout [ 12 , 15 , 16 ]. In addition, connectivity in regions associated with emotional regulation and EF predict PTSD symptoms post-trauma [ 64 ], consistent with the role of FPCN-LN in mediating the relationship between EF and PTSD chronicity.…”
Section: Discussionmentioning
confidence: 99%